Self-templating accelerates precipitation of carbamazepine dihydrate during the dissolution of a soluble carbamazepine cocrystal - Yamashita, Hiroyuki; Sun, Changquan Calvin (CrystEngComm, 2017)
Similarly organized carbamazepine (CBZ) clusters in a soluble cocrystal with glutaric acid templated the nucleation and precipitation of poorly soluble CBZ dihydrate during dissolution.